Cytogenetic Analysis of the Fish Genus Carassius Indicates Divergence, Fission, and Segmental Duplication as Drivers of Tandem Repeat and Microchromosome Evolution - Fornaini, Nicola R; Černohorská, Halina; do Vale Martins, Lívia; Knytl, Martin (Genome biology and evolution, 2024)
Fishes of the genus Carassius are useful experimental vertebrate models for the study of evolutionary biology and cytogenetics. Carassius demonstrates diverse biological characteristics, such as variation in ploidy levels and chromosome numbers, and presence of microchromosomes. Those Carassius polyploids with ≥150 chromosomes have microchromosomes, but the origin of microchromosomes, especially in European populations, is unknown. We used cytogenetics to study evolution of tandem repeats (U1 and U2 small nuclear DNAs and H3 histone) and microchromosomes in Carassius from the Czech Republic. We tested the hypotheses whether the number of tandem repeats was affected by polyploidization or divergence between species and what mechanism drives evolution of microchromosomes. Tandem repeats were found in tetraploid and hexaploid Carassius gibelio, and tetraploid Carassius auratus and Carassius carassius in conserved numbers, with the exception of U1 small nuclear DNA in C. auratus. This conservation indicates reduction and/or loss in the number of copies per locus in hexaploids and may have occurred by divergence rather than polyploidization. To study the evolution of microchromosomes, we used the whole microchromosome painting probe from hexaploid C. gibelio and hybridized it to tetraploid and hexaploid C. gibelio, and tetraploid C. auratus and C. carassius. Our results revealed variation in the number of microchromosomes in hexaploids and indicated that the evolution of the Carassius karyotype is governed by macrochromosome fissions followed by segmental duplication in pericentromeric areas. These are potential mechanisms responsible for the presence of microchromosomes in Carassius hexaploids. Differential efficacy of one or both of these mechanisms in different tetraploids could ensure variability in chromosome number in polyploids in general.
Keywords: Animals; teleost fish; polyploidie; cytogenetické vyšetření; polyploidy; histone H3; U1 and U2 snDNAs; Polyploidy; segmentové duplikace; FISH; Cyprinidae; tetraploidie; Segmental Duplications, Genomic; zvířata; Tandem Repeat Sequences; Cytogenetic Analysis; tandemové repetitivní sekvence; chromosome painting; Tetraploidy